Carbon dioxide adsorption thermodynamics and mechanisms on MCM-41 supported polyethylenimine prepared by wet impregnation method. (15th March 2015) - Wang, Weilong; Li, Jiang; Wei, Xiaolan; Ding, Jing; Feng, Haijun; Yan, Jinyue; Yang, Jianping
Highlights: Molecular simulation are used to understand wet impregnation synthesis of MBS. The mechanism of CO2 sorption on MBS has been simulated and discussed. CO2 -philic specific sorption sites of MBS with various sorption energy are discovered. Abstract: Amine-functionalized sorbents prepared by wet impregnation method shows great promises for CO2 capture from real flue gas in power plants. The objective of this work is to understand CO2 adsorption thermodynamics and mechanisms at varied polyethylenimine (PEI) loadings on mesoporous MCM-41 by wet impregnation method using a computational approach for the first time. The structures of PEI/MCM-41 sorbents were optimized using molecular dynamics (MD), and the CO2 adsorption thermodynamics at varied PEI loadings was simulated using Grand Canonical Monte Carlo (GCMC) method. Results showed a good agreement between experiments and simulation. On the surface of the MCM-41, there are high CO2 -philic sites for CO2 adsorption, which were firstly covered by PEI molecular. The functionalization groups increased the interactions of the CO2 with more PEI molecular deployed on the surface of the MCM-41, then to the center of the pore. The adsorption performance of the composite sorbents depended on the adsorption cites and the space for CO2 diffusion. The CO2 adsorption thermodynamics and mechanisms at varied PEI loadings shed lights on tuning CO2 capture performance with amine-functionalized sorbents for power plant greenhouse gas control.